2014
DOI: 10.1186/1475-2875-13-398
|View full text |Cite
|
Sign up to set email alerts
|

Severe delayed autoimmune haemolytic anaemia following artesunate administration in severe malaria: a case report

Abstract: BackgroundParenteral artesunate is recommended as first-line therapy for severe and complicated malaria. Although its efficacy has been proven, long-term safety profile is still under evaluation. Several cases of delayed haemolytic anaemia occurred after initial clinical improvement and resolution of parasitaemia in non-immune travellers and children living in endemic areas. Reports have generated concern that this phenomenon might be related to the treatment itself, either by direct toxicity or immune-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 23 publications
6
39
0
Order By: Relevance
“…23 Furthermore, artesunate-dependent antibodies were recently reported in a French patient. 13 Similar to our patients, most patients with delayed hemolysis described to date have recovered naturally. Several patients with severe anemia, however, required blood transfusions to support their recovery.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…23 Furthermore, artesunate-dependent antibodies were recently reported in a French patient. 13 Similar to our patients, most patients with delayed hemolysis described to date have recovered naturally. Several patients with severe anemia, however, required blood transfusions to support their recovery.…”
Section: Discussionsupporting
confidence: 86%
“…Among the 39 previously reported PADH cases, 14 had switched to oral artemether-lumefantrine following initial treatments such as parenteral artesunate or parenteral artesunate plus tetracyclines. 3,[12][13][14] Other combinations of ACTs included artesunate-amodiaquine following artesunate injection, 5 dihydroartemisinin-piperaquine following intramuscular artemether, 6 and artemether-lumefantrine following quinine injection plus doxycycline. 8 Only one previous case of PADH was associated with artemetherlumefantrine as the sole regimen.…”
Section: Discussionmentioning
confidence: 99%
“…Artesunate have been previously reported to be associated with neutropenia at doses higher than doses administered in our study (Bethell et al, 2010), however neutropenia was not observed with AS, ASQ or AQ during the study. This study lends support to a case report of artesunate induced auto-immune post-treatment delayed hemolysis, although this occurred in a malaria patient (Raffray et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
“…In vitro studies performed by Alzoubi et al (2014a,b) showed that the antimalarial drugs artesunate and lumefantrine have proapoptotic effect on erythrocytes, possibly through generation of oxidative stress, a feature already reported for both drugs (Xie et al, 2005; Abolaji et al, 2013). Thus, the proapoptotic effect of artesunate and lumefantrine could explain the reduction of erythrocytic blood parameters reported in healthy rats and humans (Xie et al, 2005; Kongpatanakul et al, 2009) as well as in occurrence of acute anemia in malarial patients following antimalarial drug treatment (De Nardo et al, 2013; Raffray et al, 2014; Sowunmi et al, 2015). …”
Section: Malaria and Erythrocytic Apoptosis Inducersmentioning
confidence: 99%